Respuesta :

Simplifying

3X + 10 = 6X + 40

Reorder the terms:

10 + 3X = 6X + 40

Reorder the terms:

10 + 3X = 40 + 6X

Solving

10 + 3X = 40 + 6X

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '-6X' to each side of the equation.

10 + 3X + -6X = 40 + 6X + -6X

Combine like terms: 3X + -6X = -3X

10 + -3X = 40 + 6X + -6X

Combine like terms: 6X + -6X = 0

10 + -3X = 40 + 0

10 + -3X = 40

Add '-10' to each side of the equation.

10 + -10 + -3X = 40 + -10

Combine like terms: 10 + -10 = 0

0 + -3X = 40 + -10

-3X = 40 + -10

Combine like terms: 40 + -10 = 30

-3X = 30

Divide each side by '-3'.

X = -10

Simplifying

X = -10